(untitled) (European Journal of Behavioral Sciences, 2025)
This study aimed to explore the level of aggressive behavior among high school female students in Kuwait in light of certain variables, including academic performance, residential area, and socioeconomic status. This cross-sectional study relied on the descriptive quantitative approach. The study sample consisted of 235 high school female students in Kuwait, selected using a random sampling technique. To collect the study data, an Aggressive Behavior Scale was employed, and indicators of the scale’s validity and reliability demonstrated that it possessed good and satisfactory psychometric properties. The results revealed a moderate level of aggressive behavior (overall score) among high school female students in Kuwait. Approximately 14.7% of the sample exhibited a high level of aggressive behavior, while about 14.2% showed a low level of aggressive behavior. Aggressive behavior towards oneself ranked first, followed by aggressive behavior towards others. Aggressive behavior towards property and objects, along with deviation from norms and values, ranked second. Additionally, a statistically significant negative correlation was found between academic performance and the overall score on the Aggressive Behavior Scale, as well as its following dimensions: aggressive behavior towards others, aggressive behavior towards property and objects, and deviation from norms and values. While there was a statistically significant positive correlation between academic performance and aggressive behavior towards oneself, high school female students residing in Mubarak Al-Kabeer Governorate exhibited statistically higher levels of aggressive behavior compared to other groups. Furthermore, high school female students with a medium socioeconomic status and income reported statistically higher levels of aggressive behavior compared to other groups.